Análise dos impactos socioambientais a partir da implantação dos empreendimentos de geração de energia elétrica de fonte eólica no estado da Paraíba - Silva, Wandson do Nascimento (2024)
During the 20th century and the early years of the 21st century, the world underwent various transformations, resulting in a significant energy demand from society. As a result, the need for the development of new technologies and the implementation of public policies focused on the adoption of new energy sources, particularly renewable sources, emerged. In Brazil, the energy crisis experienced in the early 2000s spurred the implementation and generation of alternative energy sources, with a particular emphasis on wind energy, which accounts for just over 13% of the national electricity generation (ANEEL, 2023). The Northeast region stands out in this context due to its geographical location and favorable conditions for wind energy generation, mainly due to the occurrence of strong winds throughout the year. Currently, the majority of wind energy generation is concentrated in the states of Rio Grande do Norte, Bahia, and Piauí. However, despite being considered a clean source of energy that does not pollute the atmosphere with greenhouse gas emissions, the implementation of wind energy projects leads to serious socio-environmental impacts, such as improper land use, deforestation, risks of electrical shocks, and visual impacts. Thus, this study aims to analyze the socio-environmental impacts resulting from the implementation of wind energy projects in the state of Paraíba. To this end, a methodological sequence based on the Geoecology of Landscapes was employed, allowing for an integrated analysis of the landscape, encompassing the constituent aspects of environmental dynamics. The results show that, despite wind energy being part of a renewable and sustainable energy matrix, the implementation and operation of wind farms lead to severe damage to natural ecosystems. The study observed the suppression of native vegetation over large areas of land, resulting in biodiversity loss; mortality of wildlife; risks of accidents due to the lack of maintenance of protective fences around the wind turbines; soil removal and landfills for road construction, leading to the emergence of erosive processes; noise pollution generated by the rotor blades' movement; and visual impacts that cause visual discomfort when it comes to the landscape. Therefore, it is essential to analyze the environmental impacts and understand the need for economic development based on sustainable aspects and environmental planning.